Solanum lycopersicum AGG 309339 TOMA ... - GLIS Of The ITPGRFA (Australian Grains Genebank, Agriculture Victoria, 2023)
Plant Genetic Resource. Taxonomy: Solanum lycopersicum Common name(s): cherry tomato Other names: Sub-arctic cherry Conserved by: Australian Grains Genebank, DEECA (AGG), Australia Local sample unique identifier: AGG 309339 TOMA Method of creation: Acquisition Date: 1997-07-01 Other identifiers: n/a,PI 451973 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...